2020
DOI: 10.1111/jfbc.13386
|View full text |Cite
|
Sign up to set email alerts
|

Correction of glycemic and oxidative stress sensors in streptozotocin induced diabetic rat model: Impact of dose dependent study of n‐butanol solvent fraction of hydro‐methanol extract of banana flower (Musa balbisiana)

Abstract: Diabetes mellitus, the very well-known chronic metabolic disorder, is highly prevalent throughout the world. In this condition, high blood glucose level is sustained for a chronic period because of decreased activity of insulin or low level of insulin. Hyperlipidemia, polyuria, polyphagia, polydypsia, oxidative stress, ketosis, hyperglycemia, nephropathy, neuropathy, and cardiovascular disorders are the major complications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Diabetes is associated with low genomic expression of anti-oxidant enzymes as well as hyper-activation of lipid peroxidation pathways (Ara et al, 2020) and this is substantiate with our results. After direct exposure to Aloe vera (L.) antioxidant enzyme activities like catalase and SOD were recovered towards the control may be due to the activation of the antioxidant enzymes after they bound to the phytomolecule (s) present in the said extract (Tripathy et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Diabetes is associated with low genomic expression of anti-oxidant enzymes as well as hyper-activation of lipid peroxidation pathways (Ara et al, 2020) and this is substantiate with our results. After direct exposure to Aloe vera (L.) antioxidant enzyme activities like catalase and SOD were recovered towards the control may be due to the activation of the antioxidant enzymes after they bound to the phytomolecule (s) present in the said extract (Tripathy et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This explanation is compatible with recently published research work by others using another plant. [18,19] Individuals with diabetes had 1.5 and 2 times higher AG and AA activities, respectively. [20] Regularization of the said enzyme activities could be a key therapeutic tool to manage post-prandial hyperglycemia.…”
Section: Resultsmentioning
confidence: 98%
“…Diabetes and obesity are the most critical metabolic and endocrine diseases associated with hyperglycemia and insulin secretion dysfunction (insulin resistance) (Ara et al, 2020; Bermudez‐Pirela et al, 2007). Numerous researches have shown that increasing fatty acids leads to β cells apoptosis.…”
Section: Introductionmentioning
confidence: 99%